Religious Certainty: Peculiarities and Pedagogical Considerations - Ariso Salgado, José María (Studies in Philosophy and Education, 2021)
This paper presents the concept of 'religious certainty' I have developed by drawing inspiration from Wittgenstein's notion of 'certainty'. After describing the particular traits of religious certainty, this paper addresses two difficulties derived from this concept. On the one hand, it explains why religious certainty functions as such even though all its consequences are far from being absolutely clear; on the other hand, it clarifies why, unlike the rest of certainties, the loss of religious certainty does not result in the collapse of the world-picture made up of all certainties. Subsequently, it analyzes to what extent the teacher can teach religious certainty by acting as a facilitator for its acquisition-if desired-particularly bearing in mind that religious certainty cannot be attained at will. These basic teaching guidelines have several advantages. First, they make it possible to know the nature of religious certainty even better. Second, and most importantly, the fact of having adopted the perspective of a teacher who tries inculcating a religious certainty contributes to detecting and preventing forms of indoctrination that, arguably, might go unnoticed even when attempting to properly present religious certainty-or rather, this way of being religious-in current schools to foster understanding thereof.
Keywords: wittgenstein; religious certainty; will; world-picture; indoctrination; JCR; Scopus